2018
DOI: 10.3389/fphys.2018.00269
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Promotes Cheliped Regeneration, Digestive Enzyme Function, and Immunity Following Autotomy in the Chinese Mitten Crab, Eriocheir sinensis

Abstract: In the pond culture of juvenile Eriocheir sinensis, a high limb-impairment rate seriously affects the culture success. Therefore, it is particularly important to artificially promote limb regeneration. This study evaluated the effects of melatonin on cheliped regeneration, digestive ability, and immunity, as well as its relationship with the eyestalk. It was found that the injection of melatonin significantly increased the limb regeneration rate compared with the saline group (P < 0.05). The qRT-PCR results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 68 publications
(79 reference statements)
0
22
0
Order By: Relevance
“…Our previous study found that melatonin can promote cheliped regeneration of E . sinensis by regulating the expression of EcR , MIH and Chi genes [20]. Therefore, in the present study we examined the expression levels of EcR , MIH and Chi genes during the cheliped regeneration process of E .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study found that melatonin can promote cheliped regeneration of E . sinensis by regulating the expression of EcR , MIH and Chi genes [20]. Therefore, in the present study we examined the expression levels of EcR , MIH and Chi genes during the cheliped regeneration process of E .…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis of Portunus trituberculatus in limb regeneration showed that limb regeneration appears to be regulated by multiple signalling pathways, the expression of genes involved in muscle growth, moult and immune-related genes up-regulated [18]. And studies reported that the process of crab cheliped regeneration is primarily dependent on the co-regulation of ecdysteroid and molting-inhibiting hormone (MIH); ecdysteroid promotes cheliped regeneration, whereas MIH inhibits cheliped regeneration [19,20]. And chitinase (Chi) plays an important role in the molting cycle of E .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Trp metabolite melatonin, affects the immune system and antioxidant defense system (ADS) of crustaceans ( 33 , 115 ). When eyestalk-ablated E. sinensis were injected with melatonin, both their immune and antioxidant capacity were enhanced in terms of increased THC and hemocyanin levels, coupled with an elevation in the activities of ALP, ACP, superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and other antioxidant enzymes ( 31 ). Melatonin injection also enhances response to oxidative damage and elimination of damaged mitochondria and hemocytes due to external stress in E. sinensis ( 32 ).…”
Section: Amino Acid Metabolism and Crustacean Immunitymentioning
confidence: 99%
“…In addition, hemocytes can adhere to pathogens, trigger phagocytosis, and produce highly toxic reactive oxygen species (ROS) (28). Our previous studies have shown that melatonin (N-acetyl-5-methoxytryptamine) can significantly improve the serum antioxidant capacity of E. sinensis (29). As the precursor of melatonin, tryptophan is an effective scavenger for free radicals and can maintain the cellular redox balance by enhancing the body's antioxidant capacity (30).…”
Section: Introductionmentioning
confidence: 99%